Pengaruh Inflasi, Suku Bunga, Debt to Asset Ratio (DAR), Price to Earning Ratio (PER), Quick Ratio (QR), dan Return on Asset (ROA) terhadap Return Saham Serta Tinjauannya dari Sudut Pandang Islam (Studi pada Perusahaan Industri Farmasi yang Tercatat di Bursa Efek Indonesia Periode 2019-2023) - Kadafi, Fadil Muharam; Rofi’i, Muhammad; Ma’sum, Ali; Muslikh, Muslikh; Budiman, Andika Nuraga; Zusryn, Alyta Shabrina (Innovative: Journal Of Social Science Research, 2025)
The purpose of this research is to study how inflation, interest rates, Debt to Asset Ratio (DAR), Price to Earning Ratio (PER), Quick Ratio (QR), and Return on Assets (ROA) impact stock returns in pharmaceutical companies. listed on the Indonesia Stock Exchange during the period 2019 to 2023. This study uses panel data regression, with the research sample consisting of seven companies. This study shows that stock returns are not influenced by inflation; interest rate no, Debt to Asset Ratio (DAR) no, Price to Earning Ratio (PER) no, Quick Ratio (QR) no, and return on assets (ROA) no.